2015
DOI: 10.1002/gcc.22284
|View full text |Cite
|
Sign up to set email alerts
|

Copy number profiling by array comparative genomic hybridization identifies frequently occurring BRCA2‐like male breast cancer

Abstract: Genomic aberrations can be used to subtype breast cancer. In this study, we investigated DNA copy number (CN) profiles of 69 cases of male breast cancer (MBC) by array comparative genomic hybridization (aCGH) to detect recurrent gains and losses in comparison with female breast cancers (FBC). Further, we classified these profiles as BRCA1-like, BRCA2-like or non-BRCA-like profiles using previous classifiers derived from FBC, and correlated these profiles with pathological characteristics. We observed large CN … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 77 publications
0
9
0
Order By: Relevance
“…Recent large-scale cross-platform projects have provided a detailed characterization of the genomic landscape of FBC (Cancer Genome Atlas Network 2012, Curtis et al 2012, Nik-Zainal et al 2016, Pereira et al 2016, Bailey et al 2018, Berger et al 2018. The Cancer Genome Atlas (TCGA) (Cancer Genome Atlas Network 2012) reported the enrichment of specific mutations in PIK3CA (47%), GATA3 (14%), MAP3K1 (13%), TP53 (12%), CDH1 (10%) and MAP2K4 (7%) with the luminal A subtype and in TP53 (31%), PIK3CA (32%) and MAP3K1 (5%) within the luminal B subtype (Gao et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Recent large-scale cross-platform projects have provided a detailed characterization of the genomic landscape of FBC (Cancer Genome Atlas Network 2012, Curtis et al 2012, Nik-Zainal et al 2016, Pereira et al 2016, Bailey et al 2018, Berger et al 2018. The Cancer Genome Atlas (TCGA) (Cancer Genome Atlas Network 2012) reported the enrichment of specific mutations in PIK3CA (47%), GATA3 (14%), MAP3K1 (13%), TP53 (12%), CDH1 (10%) and MAP2K4 (7%) with the luminal A subtype and in TP53 (31%), PIK3CA (32%) and MAP3K1 (5%) within the luminal B subtype (Gao et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study of similar size (59 MBC samples) also found that MBCs and FBCs of similar subtype shared many recurrent copy number aberrations (Piscuoglio et al 2016). Unfortunately, this study did not determine BRCA2-like status based on copy number profiles despite reporting 5% of the samples as germline BRCA2 mutated, so validation of high frequency of BRCA2-like status in MBC (Biesma et al 2015) and potential AR upregulation could not be investigated.…”
Section: Molecular Featuresmentioning
confidence: 84%
“…In a recent study, Biesma and coworkers found 22% of MBC samples investigated (15/69) had a BRCA2-like profile based on DNA copy number data indicating a significant proportion of MBCs may be susceptible to PARP inhibition therapy or specific chemotherapy regimens aimed at DNA double-strand breaks (Biesma et al 2015). In addition, with the exception of gains on chromosome X in MBC, this work found few differences between MBC and FBC (luminal-like) with respect to copy number changes (Biesma et al 2015). This is a particularly interesting finding as AR is found on chromosome X and may therefore be upregulated in these samples.…”
Section: Molecular Featuresmentioning
confidence: 99%
“…However, the relationship between P53 expression and BRCA2 Mut is less clear than that for BRCA1 Mut . Biesma et al [ 37 ] identified P53 overexpression in approximately 50% of BRCA2 Mut , whereas others reported that less than 20% of such tumors had elevated P53 [ 38 ]. Additionally, P53 overexpression was not found in BRCA2 Mut tumors in 1 report [ 39 ].…”
Section: Discussionmentioning
confidence: 99%